Peningkatan Pemurnian Minyak Jelantah melalui Sistem Adsorben Ganda: Bleaching Earth dan Karbon dari Kulit Buah Kakao (Theobroma cacao L) - Utami, Esssylia Afriyanti; Nizar, Umar Kalmar; Etika, Sri Benti (MASALIQ, 2025)
Used cooking oil (minyak jelantah) is a household and industrial waste product that poses environmental risks and undergoes significant quality degradation due to the breakdown of chemical compounds during repeated use. This study aims to evaluate the effectiveness of a combination of activated carbon derived from cocoa pod husk waste and bleaching earth in improving the quality of used cooking oil. The research was conducted experimentally in the laboratory of Universitas Negeri Padang using used cooking oil obtained from local vendors. Activated carbon was prepared by calcining cocoa pod husks at 350°C for varying durations of 30, 45, 60, and 75 minutes, followed by activation with 1M NaOH solution. The purification process was carried out in stages through the addition of activated carbon and bleaching earth under controlled heating conditions. Parameters analyzed included acid number, moisture content, density, saponification value, and functional group characterization using infrared spectroscopy (FTIR). The results indicate that the most effective adsorbent combination was achieved with activated carbon calcined for 60 minutes, which reduced the acid number from 14.92 to 5.09 mg KOH/g, decreased moisture content to 0.11%, and increased the saponification value to 75.30 mg KOH/g. The FTIR spectrum showed reduced intensity in functional groups associated with degradation, indicating effective purification. In conclusion, the combination of activated carbon from cocoa pod husk waste and bleaching earth is proven effective in improving the physicochemical quality of used cooking oil, while also demonstrating the potential for sustainable and environmentally friendly use of agricultural waste as raw material for adsorbents.